2020
DOI: 10.1111/tmi.13356
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and characteristics of HIV clusters in Ethiopia

Abstract: Objectives Ethiopia’s HIV prevalence has decreased by 75% in the past 20 years with the implementation of antiretroviral therapy, but HIV transmission continues in high‐risk clusters. Identifying the spatial and temporal trends, and epidemiologic correlates, of these clusters can lead to targeted interventions. Methods We used biomarker and survey data from the 2005, 2011 and 2016 Ethiopia Demographic and Health Surveys (DHS). The spatial‐temporal distribution of HIV was estimated using the Kulldorff spatial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Substantial spatial variation was observed in all three diseases at regional and local levels in Ethiopia. Previous studies have reported similar spatial clustering of HIV, TB and malaria in Ethiopia 13 15 53. However, the current study provided additional information in which the spatial distribution of HIV, TB and malaria overlapped in some parts of the country.…”
Section: Discussionsupporting
confidence: 45%
“…Substantial spatial variation was observed in all three diseases at regional and local levels in Ethiopia. Previous studies have reported similar spatial clustering of HIV, TB and malaria in Ethiopia 13 15 53. However, the current study provided additional information in which the spatial distribution of HIV, TB and malaria overlapped in some parts of the country.…”
Section: Discussionsupporting
confidence: 45%
“…Even though adult HIV prevalence, or the proportion of persons in a population who are living with HIV at a specific point in time, has declined at the national level, little information is available about sub-geographic areas and certain subpopulations in urban Ethiopia. Analysis of data from the 2011-2016 demographic and health survey in Ethiopia indicated that the distribution of HIV infection in Ethiopia is not random [6][7][8]. A study in one region in Ethiopia revealed that low educational status and migration status are determinants of HIV infection in Ethiopia [9].…”
Section: Introductionmentioning
confidence: 99%
“…Geospatial analysis of epidemiological data can generate precise maps of hotspot locations where HIV prevalence is concentrated [13]. Local spatial analyses can show geographic variation of the HIV epidemic and its drivers and inform targeted interventions; however, few geospatial analyses use data from subpopulations in Ethiopia [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The HIV-1 group M is responsible for the global pandemic associated with HIV; the HIV-2 strain is mainly found in West Africa, Mozambique, Angola, and southwest India (Eberle & Gürtler, 2012), and is less pathogenic than the HIV-1 strain. Geographic HIV clusters are driven by different biological and behavioural risk factors (Ying et al, 2020). In eastern and southern Africa, HIV prevalence among sex workers is extremely high; adolescent girls and young women account for 30% of new infections, and above 50% of sex workers are living with HIV (UNAIDS, 2020).…”
Section: Introductionmentioning
confidence: 99%